Антропогенні чинники екологічної кризи - Сулацкова, О. Ф.; Sulatskova, O. F. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено осмисленню проблеми екологічної кризи. Автор аналізує природу екологічної кризи загалом і в окремих її проявах, а також антропогенні чинники екологічної кризи. Зроблено такий висновок: один із найбільш дієвих чинників екологічної кризи – диспропорція між розвитком технологічного потенціалу людства й розвитком системи культурних регуляторів. This article is devoted to the comprehension of the problem of the environmental crisis. The author analyzes the nature of ecological crisis as a whole and in its individual manifestations, considering anthropogenic factors of ecological crises. Concludes that one of the most effective factors of the ecological crisis is a disproportion between the development of the technological potential of humanity and the development of a system of cultural regulators. Problems of ecological crisis it is not settled by ethical aspect, and is wider - filosofsko-world outlook, that is is philosophy and spirituality crisis. Enough big contribution to development of the crisis phenomena adds the existing contradiction of personal and public interests, dominances of regional thinking over the global. Degradation of habitat grows out not simply and not only technogenic pressure upon it, and a consequence of an impoverishment of morals of a society, blindness concerning the future consequences of the accepted style of life.
Anthropogenic Factors of Ecological Crisis
Keywords: криза; crisis; екологічна криза; environmental crisis; антропогенна криза; antropogenic crisis; проблема; a problem; екологічна катастрофа; environmental catastrophe